Analisis hubungan karies gigi dan status gizi anak usia 10-11 tahun di SD Athirah, SDN 1 Bawakaraeng dan SDN 3 Bangkala - Asmawati Asmawati; Fransario A. Pasolon (DiscoverSys Inc., 2007)
Tooth decay is a serious problem in health of tooth and oral inIndonesia with finite prevalence up to 90.05% mainly at school age ofchildren. Tooth decay can be caused by various factors, such asmicroorganism, food, tooth, saliva, and time, and supported by variousother factors like race, age, gender, and genes. Children's dental cariesis frequently caused by the habit to consume food cariogenic whichdoes not only affect tooth but also the nutrition status of child. The aim of this analytic observational study was to know the prevalenceof tooth decay, nutrition status, and the relation of dental caries andnutrition status at school age child ( 0.05 . This study involved 180samples (60 samples from SD Athirah, SDN 1 Bawakaraeng, and SDN3 Bangkala respectively). These three elementary schools in wereselected based on their socio-economic status. SD Athirah representsthe high socio economic status, SDN 1 Bawakaraeng the middle socioeconomicstatus,and SDN 3 Bangkala the lowest status. Dental cariesstatus was investigated with DMF-T index and nutrition status with BM/Aindex. Data were analyzed using chi-square test. Results of the studywere as follows from the three schools, only SD Athirah shows relationbetween dental caries and nutrition status with its significance value0.009 (p<0.05). no significance relation between dental caries andnutrition status at SDN 1 Bawakaraeng with p=0.536 (p>0.05). Thesimilar relation was found at SDN 3 Bangkala with p= 0.926 (p>0.05).